IMPLEMENTASI KEBIJAKAN DISTRIBUSI FORMULIR C. PEMBERITAHUAN-KWK SEBAGAI LAYANAN PEMENUHAN HAK KONSTITUSIONAL PEMILIH PEMILIHAN TAHUN 2024 - Syakban, Ory Sativa (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
Abstract: This study aims to evaluate the extent to which the distribution policy of Form C.Pemberitahuan-KWK is effective in supporting the fulfilment of voters' constitutional rights in the 2024 Simultaneous Elections in West Sumatra Province. This policy was implemented to serve more than 4 million voters, involving 107,028 policy implementers at various levels. The focus of the study lies in how the form is used as an information service medium to encourage voter participation in the local democratic process. The method used is a mixed-method approach with an exploratory sequential design, beginning with descriptive-analytical qualitative analysis followed by limited quantitative mapping. Data was obtained through legal document studies, election administration reports, and official KPU archives. The research findings indicate that, first, the distribution of the forms was designed through a systematic top-down system, supported by operational procedures, significant resource allocation, and structured communication from the central KPU to the KPPS. Second, these forms are an important means of accessing election information, but they only reach voters on the DPT and do not target additional voters or those who are not yet registered. Third, the KPU's hierarchical and solid organisational structure enables the rapid and equitable implementation of policies. Fourth, there is a discrepancy between the success of form distribution and voter turnout. This study recommends the need for finalised information content and improvements to the Form C.Pemberitahuan-KWK, as well as expanding its distribution scope to ensure more inclusive and informative voting rights in the future.Keywords: Election Information, Public Policy, Voter Notification, Voter Participation, 2024 Election.